2012
DOI: 10.1007/s00592-012-0428-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of leptin and its long-form receptor in the marginal cutaneous tissues of diabetic foot ulcers

Abstract: To investigate the relationship between the expression of leptin and its long-form receptor, OB-RL, and wound healing in diabetic foot ulcers. Biopsies from 10 patients with diabetic foot ulcers (DU group), 10 with non-diabetic foot ulcers (NDU group), and 10 with normal skin (normal control, NC group) were examined. Leptin and OB-RL mRNA and protein levels were assessed using RT-PCR and immunohistochemistry analyses, respectively. The cuticle thickness was significantly greater, and the epidermal layer was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Leptin protein expression was significantly higher in the DU and NDU than in the NC group ( p < 0.001), whereas OB-RL (leptin receptor-long form) mRNA and protein expressions were significantly lower in the DU group and significantly higher in the NDU group. Diabetic foot ulcer duration was negatively correlated with OB-RL protein expression [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Leptin protein expression was significantly higher in the DU and NDU than in the NC group ( p < 0.001), whereas OB-RL (leptin receptor-long form) mRNA and protein expressions were significantly lower in the DU group and significantly higher in the NDU group. Diabetic foot ulcer duration was negatively correlated with OB-RL protein expression [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also a general pharmacological fact that whenever the first messenger is decreased then its receptor is increased (upregulation-downregulation). Moreover, Cao et al 20 reported that decreased Ob-R expression might be related to the negative feedback resulting from high leptin protein concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Topical administration of leptin significantly promoted wound healing, increased angiogenesis in dermis and activated proliferation and differentiation of epidermal keratinocytes [75]. Leptin protein expression was significantly higher in both diabetic and non-diabetic foot ulcers [76].…”
Section: Fish Oil and Leptin And Adiponectinmentioning
confidence: 99%